Integrative Analysis of lncRNA-mRNA Co-expression Provides Novel Insights Into the Regulation of Developmental Transitions in Female Varroa destructor - Wu, Jiang-Li; Hu, Ruo-Yang; Li, Nan-Nan; Tan, Jing; Zhou, Chun-Xue; Han, Bin; Xu, Shu-Fa (Frontiers in Ecology and Evolution, 2022)
Varroa destructor is a major pathogenic driver of the Western honey bee colony losses globally. Understanding the developmental regulation of Varroa is critical to developing effective control measures. Development is a complex biological process regulated by numerous genes and long non-coding RNAs (lncRNAs), however, the underlying regulation of lncRNAs in Varroa development remains unknown. Here, we analyzed the RNA-Seq data derived from the four stages of Varroa females in the reproductive phase (egg, protonymph, deutonymph, and adult). The identified differentially expressed mRNAs and lncRNAs exhibited a stage-specific pattern during developmental transitions. Further functional enrichment established that fat digestion and absorption, ABC transporters, MAPK signaling pathway, and ubiquitin–proteasome pathway play key roles in the maturation of Varroa females. Moreover, the lncRNAs and mRNAs of some pivotal genes were significantly up-regulated at deutonymph stage, such as cuticle protein 65/6.4/63/38 and mucin5AC, suggesting the deutonymph is the key stage of metamorphosis development and pathogen resistance acquisition for Varroa females. Our study provides novel insights into a foundational understanding of Varroa biology.